Subcutaneous phaeohyphomycosis: A rare case - Zahruddin Ahmad; Diah Mira Indramaya; Yuri Widia; Sylvia Anggraeni; Linda Astari; Evy Ervianti; Sunarso Suyoso (PAGEPress Publications, 2019)
Phaeohyphomycosis is a rare fungal infection caused by melanized fungi which usually involve the skin and subcutaneous tissue. It is an infrequent cause of infection in human beings. Common clinical manifestations are subcutaneous cystic swellings, which is localized, characterized by subcutaneous asymptomatic nodular lesions that develop after traumatic implantation of fungus from contaminated soil, thorns or wood splinters, especially on extremities. We report a case of subcutaneous phaeohyphomycosis presenting as multiple cystic swellings over the left lower leg with unknown predisposing factors. At first, the patient was misdiagnosed as soft tissue tumor and subcutaneous tuberculosis, then got surgical and anti-tuberculosis therapy respectively, but there was no improvement. Further investigation revealed granulomatous inflammation on histopathology examination and black-coloured colonies identifed as Exophiala dermatitidis on fungal culture. This case of phaeohyphomycosis was successfully treated by itraconazole monotherapy without surgical excision and still under follow-up.